Personalized Healthcare: Expandable Polymer Assisted Wearable Personalized Medicinal Platform (Adv. Mater. Technol. 10/2020). Issue 10 (12th October 2020) - Babatain, Wedyan; Gumus, Abdurrahman; Wicaksono, Irmandy; Buttner, Ulrich; El‐atab, Nazek; Rehman, Mutee Ur; Qaiser, Nadeem; Conchouso, David; Hussain, Muhammad Mustafa
Abstract : In article number 2000411, Muhammad Mustafa Hussain and co‐workers demonstrate a wearable personalized medicinal platform built on microfluidics, which gathers a variety of symptoms and vitals from the user's body. Then an artificial intelligence enabled formulation and preparation of a variety of medicine, vitamins or nutrients are conducted in‐situ and delivered transdermally.